Holocaust roadscapes: Retracing the "death marches" in contemporary Europe - Cole, Tim (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l’Université Laval, 2013)
During the final year of the war, mass evacuations westwards from concentration camps on foot brought the European road network into the orbit of Holocaust landscapes. The routes of these so-called “death marches” that criss-crossed Europe have been followed by a wide variety of pilgrims, ranging from Holocaust survivors retracing former journeys they made half a century before (oftentimes accompanied by family members, and in some cases, documentary filmmakers), through organized groups of Jews and Christians, to visual artists. While motivated by very different concerns, all share assumptions that the encounter with place – an authentic site of wartime atrocity – shrinks time, merging past and present (and future). Such notions of the possibility of direct access to the past are heightened by the haptic and embodied experiences of place that are central to walking. The individuals and groups I examine aspire, quite literally, to follow in the footsteps of the victims, walking on the very same ground they walked. While these attempts at shrinking or “fixing” time have been seen variously as more or less successful, all share an assumption of the potential intersections of past, present and future in these seemingly most ordinary of memoryscapes.